AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-2010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aircraft Separation Reduction Potential for Arrivals Facilitated by Plate Lines Following the RECAT-EU Methodology

Abstract: Wake vortex related minimum aircraft separations for arrivals were evaluated utilizing plate lines. A plate line consists of a series of vertical plates placed in front of the runway that accelerate the decay of wake vortices. This study evaluates the potential to reduce minimum aircraft separations and the potential to increase safety due to the accelerated vortex decay. The presented method follows the methodology of the proposal for revised wake turbulence categorization RECAT-EU as much as possible in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In the next step, for each individual combination of leader and follower aircraft type, the RMC is calculated that would result OGE when applying the reduced IGE separation with Plate Lines also for OGE. The reduced IGE separation when using Plate Lines (IGE-PL separation) had been calculated previously as published in [11] and described in section 2. This IGE-PL separation and the resulting RMC for the OGE case are shown in Fig.…”
Section: Methodology Of the Analysis Considering Ige And Ogementioning
confidence: 99%
See 3 more Smart Citations
“…In the next step, for each individual combination of leader and follower aircraft type, the RMC is calculated that would result OGE when applying the reduced IGE separation with Plate Lines also for OGE. The reduced IGE separation when using Plate Lines (IGE-PL separation) had been calculated previously as published in [11] and described in section 2. This IGE-PL separation and the resulting RMC for the OGE case are shown in Fig.…”
Section: Methodology Of the Analysis Considering Ige And Ogementioning
confidence: 99%
“…The results of that previous study shall only be recapitulated as far as required to understand the combined analysis in and out of ground effect as presented in section 3. Details on the previous study can be found in references [11] and [12].…”
Section: Models and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to RECAT, other current research includes work on plate lines, also with the ultimate goal of increasing capacity. Plate lines are an array of vertical plates placed in front of a runway to accelerate the decay of wake vortices and, thus, to reduce the required wake separation [7]. Overall, the physics of wake vortices is well researched and understood and the field is still active.…”
Section: Introductionmentioning
confidence: 99%